A self-repairing and self-cleaning glass waterproofing agent and its preparation method and application

By forming a transparent film with a lower surface tension than water on the glass surface, a coordination network is formed with H3BO3@SiO2 material and fluoropolysiloxane oligomer, and through functional polysiloxane modification, the existing glass surface has poor durability and stability durability and stability, and the self-repair and self-cleaning effect of glass surfaces is achieved.

CN116282943BActive Publication Date: 2025-04-22INSTITUTE OF APPLIED CHEMISTRY JIANGXI ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211569648.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-04-22
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

The existing glass surface lacks waterproof, oilproof and self-cleaning functions, and the prior art has problems of poor durability and stability when improving the waterproof, anti-fog and self-cleaning performance of the glass surface.

Method used

By preparing a self-healing self-cleaning glass waterproofing agent, the waterproofing agent forms a completely transparent film with a lower surface tension than water on the glass surface. It uses H3BO3@SiO2 material to form a coordination network with fluoropolysiloxane oligomers, and through functional polysiloxane modification, a solid microscopic nanostructure is prepared to improve material stability and achieve superhydrophobicity.

Benefits of technology

It realizes long-term waterproof, anti-fog and self-cleaning performance of the glass surface, improves durability and stability, and enables the glass surface to be automatically repaired and cleaned.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
  • Figure SMS_10
    Figure SMS_10
  • Figure SMS_11
    Figure SMS_11
Patent Text Reader

Abstract

The present invention belongs to the technical field of glass surface treatment, and specifically relates to a self-repairing and self-cleaning glass waterproofing agent, which includes the following preparation steps: (1) preparing H3BO3@SiO2 material; (2) taking H3BO3@SiO2 material and adding it to an organic solvent mixed with fluorine-containing polysiloxane oligomer, heating and refluxing, removing the organic solvent, and then adding ethanol to dissolve it for standby use; (3) fully dissolving the functional polysiloxane oligomer and the curing agent in the alcohol solvent, then dripping them into the solution of step (2) for reaction, ultrasonic treatment, and obtaining a waterproofing agent. The waterproofing agent prepared by the present invention forms a layer of completely transparent film with a surface tension lower than that of water on the glass surface, which greatly improves the durability and stability of the waterproof, anti-fogging and self-cleaning properties of the glass surface, and gives it the ability of rapid self-repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass surface treatment, and in particular relates to a self-repairing and self-cleaning glass waterproofing agent and a preparation method and application thereof. Background Art

[0002] Glass is widely used in production and life in the fields of construction engineering, home design, etc. due to its good perspective and light transmission properties, especially in doors and windows, bathroom glass, and windshields. Existing glass generally does not have functions such as waterproof, oil-proof and self-cleaning. Since glass is in contact with the environment for a long time, how to improve the waterproof, anti-fogging and self-cleaning properties of the glass surface has become a research hotspot. Due to its unique structure, silicone polymers have excellent heat resistance, weather resistance, electrical insulation, hydrophobicity, physiological inertness, high and low temperature fluidity, antioxidant stability and other properties. There are many studies on improving glass antifouling, but silicone polymers are not compatible with organic materials. In terms of viscosity and shear stability, high molecular weight polysiloxanes are more likely to produce a decrease in apparent viscosity at high shear rates than low molecular weight polysiloxanes, which limits its application field. Many methods for improving the waterproof, anti-fogging and self-cleaning properties of glass surfaces have been reported in the literature, but there are still problems such as poor durability and poor stability. Summary of the invention

[0003] The purpose of the present invention is to provide a self-repairing and self-cleaning glass waterproofing agent and a preparation method thereof, and to use the agent to form a completely transparent film with a surface tension lower than that of water on the glass surface, thereby overcoming the shortcomings of the existing glass surface waterproofing, anti-fogging and self-cleaning performance, poor durability and stability.

[0004] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0005] A method for preparing a self-repairing and self-cleaning glass waterproofing agent comprises the following steps:

[0006] (1) Ethanol and ammonia water are stirred evenly at room temperature, then a mixed solution of ethyl orthosilicate and deionized water is added, and ultrasonic dispersion is performed in a water bath at room temperature for 2 h to 4 h to form a silica sol solution, and then H3BO3 is dropped into the solution, and the pH value is adjusted to 9 to 10, and the solution is stirred and reacted at 60°C to 90°C for 2 h to 4 h to obtain H3BO3@SiO2 material;

[0007] (2) Add H3BO3@SiO2 material to an organic solvent mixed with fluorinated polysiloxane oligomer, heat and reflux for 2 h to 6 h, remove the organic solvent, and then add ethanol to fully dissolve it for later use;

[0008] (3) The functional polysiloxane oligomer and the curing agent are fully dissolved in an alcohol solvent, and then added dropwise to the solution of step (2), reacted at 30° C. to 60° C. for 2 h to 4 h, and then ultrasonically treated at room temperature for 30 min to 60 min to obtain a waterproofing agent.

[0009] In a preferred example, in step (1), the volume ratio of ethanol, ammonia water, tetraethyl orthosilicate and deionized water is 20-50:1:20-25:20-30.

[0010] In a preferred example, in step (2), the structural formula of the fluorine-containing polysiloxane oligomer is:

[0011] .

[0012] In a preferred example, in step (2), the mass ratio of the H3BO3@SiO2 material to the fluorinated polysiloxane oligomer is 1-5:1-5, the mass volume ratio of the fluorinated polysiloxane oligomer to the organic solvent is 1-5:5-10 g / L, and the volume ratio of the organic solvent to ethanol is 50-100:1-50.

[0013] In a more preferred example, the organic solvent is one of acetone, methyl formate and butyl acetate.

[0014] In a preferred example, in step (3), the structural formula of the functional polysiloxane oligomer is:

[0015] .

[0016] In a preferred example, in step (3), the mass ratio of the functional polysiloxane oligomer to the curing agent is 10:1, and the mass volume ratio of the functional polysiloxane oligomer to the alcohol solvent is 50:3-5 g / L.

[0017] In a more preferred example, the curing agent is one of triethanolamine, triethylenetetramine, and N-dimethylaniline.

[0018] Based on a general inventive concept, another object of the present invention is to provide a self-repairing and self-cleaning glass waterproofing agent prepared by the above preparation method and its application. The use steps of the glass waterproofing agent are as follows:

[0019] S1. Glass cleaning

[0020] Use detergent to clean and remove dirt. After cleaning, rinse with clean water to remove any detergent residue and let it dry naturally.

[0021] S2. Finishing

[0022] Spray the self-repairing and self-cleaning glass waterproofing agent evenly on the glass surface, dry it for 10 to 30 minutes after evenly applying, and automatically solidify it into a film at room temperature. After 10 to 30 minutes, wash the glass surface with clean water.

[0023] In the present invention, the H3BO3@SiO2 material prepared under specific conditions forms a coordination network with a fluorinated polysiloxane oligomer, which is then modified with a functional polysiloxane to prepare a strong micro-nanostructure, improve the material stability, and achieve super-hydrophobicity; the structure of the H3BO3@SiO2 material provides sufficiently strong hydrogen bonds and the modified functional polymer alcohol hydroxyl, amino group and hydroxyl group on the glass surface react to form a strong chemical bond, thereby improving the adhesion between the two interfaces and improving the durability. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in conjunction with specific embodiments, but the present invention is not limited to these embodiments. It should be noted that, under the premise of not conflicting, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. In the present invention, unless otherwise specified, all parts and percentages are mass units, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, if not otherwise specified, are conventional methods in the art.

[0025] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0026] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values ​​and all integers and fractions within the range.

[0027] Example 1

[0028] A self-repairing and self-cleaning glass waterproofing agent, the preparation method of which comprises the following steps:

[0029] (1) 70 L of ethanol and 2 L of ammonia water were stirred evenly at room temperature, and then a mixed solution of 45 L of ethyl orthosilicate and 50 L of deionized water was added, and ultrasonic dispersion was performed in a water bath at room temperature for 3 h to form a silica sol solution, and then H3BO3 was dropped into the solution, and the pH value was adjusted to 9.5. The solution was stirred and reacted at 75 °C for 3 h to obtain H3BO3@SiO2 material;

[0030] (2) Take 300 mg of H3BO3@SiO2 material and add it to 750 mL of methyl formate mixed with 300 mg of fluorinated polysiloxane oligomer, heat and reflux for 4 h to remove methyl formate, then add ethanol to fully dissolve it and set aside;

[0031] The structural formula of the fluorinated polysiloxane oligomer is:

[0032] ;

[0033] (3) 0.5 g of functional polysiloxane oligomer and 0.05 g of triethylenetetramine were fully dissolved in methanol, and then added dropwise to the solution of step (2), reacted at 45° C. for 3 h, and then ultrasonically treated at room temperature for 45 min to obtain a waterproofing agent;

[0034] The structural formula of the functional polysiloxane oligomer is:

[0035] .

[0036] Example 2

[0037] A self-repairing and self-cleaning glass waterproofing agent, the preparation method of which comprises the following steps:

[0038] (1) 100 L of ethanol and 2 L of ammonia water were stirred evenly at room temperature, and then a mixed solution of 40 L of ethyl orthosilicate and 60 L of deionized water was added, and ultrasonic dispersion was performed in a water bath at room temperature for 2 h to form a silica sol solution, and then H3BO3 was dropped into it, and the pH value was adjusted to 10. The reaction was stirred at 60 °C for 4 h to obtain H3BO3@SiO2 material;

[0039] (2) Take 500 mg of H3BO3@SiO2 material and add it to 500 mL of butyl acetate mixed with 500 mg of fluorinated polysiloxane oligomer, heat and reflux for 2 h, remove butyl acetate, and then add ethanol to fully dissolve it for later use;

[0040] The structural formula of the fluorinated polysiloxane oligomer is:

[0041] ;

[0042] (3) 0.5 g of functional polysiloxane oligomer and 0.05 g of N-dimethylaniline were fully dissolved in ethanol, and then added dropwise to the solution of step (2), reacted at 60° C. for 2 h, and then ultrasonically treated at room temperature for 60 min to obtain a waterproofing agent;

[0043] The structural formula of the functional polysiloxane oligomer is:

[0044] .

[0045] Example 3

[0046] A self-repairing and self-cleaning glass waterproofing agent, the preparation method of which comprises the following steps:

[0047] (1) 40 L of ethanol and 2 L of ammonia water were stirred evenly at room temperature, and then a mixed solution of 50 L of ethyl orthosilicate and 40 L of deionized water was added, and ultrasonic dispersion was performed in a water bath at room temperature for 4 h to form a silica sol solution, and then H3BO3 was dropped into the solution, and the pH value was adjusted to 9. The solution was stirred and reacted at 90 °C for 2 h to obtain H3BO3@SiO2 material;

[0048] (2) Take 100 mg of H3BO3@SiO2 material and add it to 1000 mL of acetone mixed with 100 mg of fluorinated polysiloxane oligomer, heat and reflux for 6 h, remove the acetone, and then add ethanol to fully dissolve it for later use;

[0049] The structural formula of the fluorinated polysiloxane oligomer is:

[0050] ;

[0051] (3) 0.5 g of functional polysiloxane oligomer and 0.05 g of triethanolamine were fully dissolved in propanol, and then added dropwise to the solution of step (2), reacted at 30° C. for 4 h, and then ultrasonically treated at room temperature for 30 min to obtain a waterproofing agent;

[0052] The structural formula of the functional polysiloxane oligomer is:

[0053] .

[0054] Comparative Example 1

[0055] (1) 70 L of ethanol and 2 L of ammonia water were stirred evenly at room temperature, and then a mixed solution of 45 L of ethyl orthosilicate and 50 L of deionized water was added, and ultrasonic dispersion was performed in a water bath at room temperature for 3 h to form a silica sol solution, and then H3BO3 was dropped into the solution, and the pH value was adjusted to 8.9. The solution was stirred and reacted at 75 °C for 3 h to obtain H3BO3@SiO2 material;

[0056] The rest is the same as Example 1.

[0057] Comparative Example 2

[0058] (1) 70 L of ethanol and 2 L of ammonia water were stirred evenly at room temperature, and then a mixed solution of 45 L of ethyl orthosilicate and 50 L of deionized water was added, and ultrasonic dispersion was performed in a water bath at room temperature for 3 h to form a silica sol solution, and then H3BO3 was dropped into the solution, and the pH value was adjusted to 10.1. The solution was stirred and reacted at 75 °C for 3 h to obtain H3BO3@SiO2 material;

[0059] The rest is the same as Example 1.

[0060] Comparative Example 3

[0061] (1) 70 L of ethanol and 2 L of ammonia water were stirred evenly at room temperature, and then a mixed solution of 45 L of ethyl orthosilicate and 50 L of deionized water was added, and ultrasonic dispersion was performed in a water bath at room temperature for 3 h to form a silica sol solution, and then H3BO3 was dropped into the solution, and the pH value was adjusted to 9.5. The solution was stirred and reacted at 59 °C for 3 h to obtain H3BO3@SiO2 material;

[0062] The rest is the same as Example 1.

[0063] Comparative Example 4

[0064] (1) 70 L of ethanol and 2 L of ammonia water were stirred evenly at room temperature, and then a mixed solution of 45 L of tetraethyl orthosilicate and 50 L of deionized water was added, and ultrasonic dispersion was performed in a water bath at room temperature for 3 h to form a silica sol solution, and then H3BO3 was dropped into the solution, and the pH value was adjusted to 9.5. The solution was stirred and reacted at 91 °C for 3 h to obtain H3BO3@SiO2 material;

[0065] The rest is the same as Example 1.

[0066] Test Example 1

[0067] The waterproofing agents prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were applied to glass samples, and the contact angles of the obtained samples were measured using a contact angle meter (CAM101 from KSV, Finland). The water droplets on the surface of the glass samples were optically photographed using the CAM101 lens, with a measurement accuracy of ±0.1°. The test environment was (23±2)°C, RH (50±5)%, and the test method was based on the sessile drop method, the principle of which was to place a water droplet on the glass surface according to Young's equation, the volume of the water droplet was controlled to be 2 to 3 μl, and the test was completed within 2 seconds of the droplet contacting the glass. The measured experimental data were compared with the data of the FY hydrophobic glass sample provided by the automotive glass supplier, and the results are shown in Table 1 below.

[0068] Table 1 Contact angle experimental data and comparison with FY hydrophobic glass sample data

[0069]

[0070] It can be seen from the results in Table 1 that the initial contact angle of the FY sample is 101.80°, while the initial contact angle of the sample of the present invention ranges from 109.09° to 109.25°, which is 7.29° to 7.45° higher than that of the FY sample.

[0071] Test Example 2

[0072] The waterproofing agents prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were applied to glass samples, and the transmittance, haze, coating adhesion, RCA abrasion resistance and hardness of the obtained samples were measured respectively according to national standards. The results are shown in Table 2 below.

[0073] Table 2 Test results of transmittance, haze, coating adhesion, RCA abrasion resistance and hardness

[0074]

[0075] Test Example 3

[0076] The waterproofing agents prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were applied to glass samples, and the self-repairing properties of the obtained samples were measured. The results are shown in Table 3 below.

[0077] Table 3 Self-repair performance test results

[0078]

[0079] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a self-repairing and self-cleaning glass waterproofing agent, characterized in that: The steps include: (1) Ethanol and ammonia water are stirred evenly at room temperature, then a mixed solution of ethyl orthosilicate and deionized water is added, and ultrasonic dispersion is performed in a water bath at room temperature for 2 h to 4 h to form a silica sol solution, and then H3BO3 is dropped into the solution, and the pH value is adjusted to 9 to 10, and the solution is stirred and reacted at 60°C to 90°C for 2 h to 4 h to obtain H3BO3@SiO2 material; (2) Add H3BO3@SiO2 material to an organic solvent mixed with fluorinated polysiloxane oligomer, heat and reflux for 2 h to 6 h, remove the organic solvent, and then add ethanol to fully dissolve it for later use; The mass ratio of the H3BO3@SiO2 material to the fluorinated polysiloxane oligomer is 1-5:1-5, the mass volume ratio of the fluorinated polysiloxane oligomer to the organic solvent is 1-5:5-10, and the volume ratio of the organic solvent to ethanol is 50-100:1-50; (3) fully dissolving the functional polysiloxane oligomer and the curing agent in an alcohol solvent, then dropwise adding the mixture to the solution of step (2), reacting at 30° C. to 60° C. for 2 h to 4 h, and then ultrasonically treating the mixture at room temperature for 30 min to 60 min to obtain a waterproofing agent; The structural formula of the functional polysiloxane oligomer is: 。 2. The method for preparing a self-repairing and self-cleaning glass waterproofing agent according to claim 1, characterized in that: In step (1), the volume ratio of ethanol, ammonia water, tetraethyl orthosilicate and deionized water is 20-50:1:20-25:20-30.

3. The method for preparing a self-repairing and self-cleaning glass waterproofing agent according to claim 1, characterized in that: In step (2), the structural formula of the fluorinated polysiloxane oligomer is: 。 4. The method for preparing a self-repairing and self-cleaning glass waterproofing agent according to claim 1, characterized in that: The organic solvent is one of acetone, methyl formate and butyl acetate.

5. The method for preparing a self-repairing and self-cleaning glass waterproofing agent according to claim 1, characterized in that: In step (3), the mass ratio of the functional polysiloxane oligomer to the curing agent is 10:1, and the mass volume ratio of the functional polysiloxane oligomer to the alcohol solvent is 50:3-5 g / L.

6. The method for preparing a self-repairing and self-cleaning glass waterproofing agent according to claim 5, characterized in that: The curing agent is one of triethanolamine, triethylenetetramine and N-dimethylaniline.

7. The self-repairing and self-cleaning glass waterproofing agent prepared by the preparation method according to any one of claims 1 to 6.

8. An application of the self-repairing and self-cleaning glass waterproofing agent as claimed in claim 7, characterized in that: The steps to use are as follows: S1. Glass cleaning Use detergent to clean and remove dirt. After cleaning, rinse with clean water to remove any detergent residue and let it dry naturally. S2. Finishing Spray the self-repairing and self-cleaning glass waterproofing agent evenly on the glass surface, dry it for 10 to 30 minutes after evenly applying, and automatically solidify it into a film at room temperature. After 10 to 30 minutes, wash the glass surface with clean water.

Citation Information

Patent Citations

  • Silica glass preparation method

    CN104402198A

  • Water-repellant glass products and process for the production thereof

    US5415927A